ANTI-RELIGIOUS PROPAGANDA IN THE PERIODICAL PRESS 1953-1956 (Academicia Globe: Inderscience Research, 2022)
The article deals with the activities of the periodical press of the Soviet government and anti-religious propaganda on the territory of Uzbekistan.